(3EYOGO GdeOQH GdQjGVj aj QjGVI GdchfZ ah Hjf GdhGbY hGdeCehds - (3CMeO ahRj(B, (3jGSjf s ((3GdGScfOQjI (B:s (3YGde GdQjGVI (B,s, 2019)
(3GdeOQH GdQjGVj h NUGFUg h GdhGbY GdaYdj aj aj EYOGOg , h JWQb ddHQfGeL GdebJQM aj EYOGO eOQH dQjGVI GdchfZ ah h ebJQM dHYV eMJhi ebQQGJ GdHQfGeL GdJOQjHj aj EYOGO eOQH GdchfZ ah (B.s
(3eQGLY s
Keywords: (3GdJOQjH GdQjGVjs; (3GdQjGVI GdHOfjIs; (3GdchfL ah s